STUDENTS’ ATTITUDES AND PERCEPTIONS TOWARDS MATHEMATICS: THE CASE OF SECONDARY SCHOOLS IN BORANA ZONE, ETHIOPIA - Assen, Awol (Universitas Papua, 2020)
Mathematics is an essential field of science applied in nearly all areas of knowledge and individuals’ daily lives. Therefore, understanding students’ attitudes towards it and affecting their mathematics performance is an essential step for appropriate intervention to make the subject enjoyable. This paper aims to give a comprehensive picture of students’ attitudes towards mathematics and factors that affect their attitude and achievement. To achieve this objective, purposive and random sampling techniques were used. A questionnaire measuring students’ attitudes and their achievement in the subject was distributed to sample students in secondary schools. Data were collected using a questionnaire that was validated, pilot tested, and its reliability was determined. The data were analyzed using descriptive statistics. Students were asked to respond to a 5-point Likert scale questionnaire that includes factors that affect the teaching practice, teachers’ attribution, classroom climate, and students’ concern as a contributing factor for their attitude towards mathematics. Besides, five free-response questions were also included to get an in-depth view of students towards mathematics. Results indicated that students have an almost positive attitude towards mathematics. Factors contributing to poor performance include lack of practice, language deficiency, societal influence, comprehensive content of the subject, lack of background on the course, development of examination in mathematics, absence of tutorial, the need for more recreation, and lack of confidence. Students’ attitude towards mathematics has determined students’ achievement directly as well as the perspective of students, and their achievements are interdependent.